ANALISIS PENGENDALIAN KUALITAS PRODUK CACAT HOUSING PADA PT XYZ - Ramadhany, Sri wulan; Sumantika , Arsyad (LPPM Universitas Putera Batam, 2022)
The method used is Statistical Process Control (SPC) and FTA (Fault Tree Analysis) methods. Then, it analyzes for improvements with 5W +1H. The SPC method is useful to repair or reduce the number of defective products, while FTA is used to analyze the causes of product defects. 5W + 1H analysis is used to analyze the solutions that can be given. Total production for the period September 2020 - August 2021 is 656,828 pcs with an average production of 54,735 pcs and the number of defective products is 7084 pcs. The types of product defects critical to quality are over glue 65%, less glue 19% and light guide gap 4%. The number of production defects that are over glue of 4579 pcs., the defects of less glue of 174 pcs and defects of light guide gap of 87 pcs. The control chart explains that the housing process is in an uncontrolled condition because there are 8 points that cross the control limits, namely October, November and December 2020. In January, February, April, June and July 2021. The DPMO value is 3,595.055 and the value is 3,595.055 and the value of sigma is 4.187σ. Proposed improvements are made by checking the quality regularly and carefully both on the equipment and machines that will be used